Mind-Body Therapies From Traditional Chinese Medicine: Evidence Map - Fogaça, Lissandra Zanovelo; Portella, Caio Fabio Schlechta; Ghelman, Ricardo; Abdala, Carmen Verônica Mendes; Schveitzer, Mariana Cabral (Frontiers in Public Health, 2021)
Background: Mind-Body Therapies of Traditional Chinese Medicine includes several intervention types and combine physical poses with conscious relaxation and breathing techniques. The purpose of this Evidence Map is to describe these different interventions and report related health outcomes. Methods: This evidence map is based on the 3iE Evidence Gap Map methodology. We searched 7 electronic databases from inception to November 2019 and included systematic reviews only. Systematic reviews were analyzed based on AMSTAR 2. We used Tableau to graphically display confidence level, number of reviews, outcomes and effects. Results: The map is based on 116 systematic reviews and 44 meta-analysis. Most of the reviews were published in the last 5 years. The most researched interventions were tai chi, tai chi chuan and qi gong. The reviews presented the following confidence levels: 72 high, 71 moderate, 22 low and 7 critically low. Every outcome effect was classified: 46.8% as potential positive; 38.1% as positive; 8.5% as no effect; 3.9% as mixed and 1.5% as negative. Positive effects were related to chronic diseases; mental indicators and disorders; vitality, well-being and quality of life. Positive potential effects were related to Parkinson’s disease, hypertension, joint pain, cognitive performance and sleep quality. Mixed effects justify further research, especially in the following areas: acupressure for nausea and vomiting; tai chi and qi gong for diabetes, low back pain and schizophrenia. Conclusions: Mind-Body Therapies from Traditional Chinese Medicine have been applied in different areas and this Evidence Map provides an easy visualization of valuable information for patients, professionals and policy-makers, in order to promote evidence-based complementary therapies.